Demographic Profile of all the Patients who have undergone PCI in Norvic International Hospital between January 2001 and Mid March 2008 - Rawat, Bharat; Bhatta, Yadav; Jaiswal, JP; Rajbhandari, Shekhar; Acharya, Nandita G; Dhakal, Saroj; Bhusal, Laxman; Shrestha, Prativa; Shrestha, Laxmi (Nepalese Heart Journal, 2008)
Norvic International Hospital has been providing interventional cardiology care for the last seven years. This study has been done to evaluate the demographic profile of all the patients who have undergone PCI in this hospital between January 2001 and mid March 2008.